2016
DOI: 10.1371/journal.pone.0168256
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Enrichment on Perineuronal Nets in the Prefrontal Cortex following Early and Late Abstinence from Sucrose Self-Administration in Rats

Abstract: Perineuronal nets (PNNs) are aggregates of extracellular matrix that form structures surrounding a subset of GABAergic interneurons. The staining intensity of PNNs appears to be related to plasticity. Environmental enrichment (EE) influences plasticity during adulthood: EE decreases the rewarding effects of drugs of abuse and diminishes both drug- and sucrose-seeking behavior. We determined the impact of EE on PNN intensity in the medial prefrontal cortex (mPFC) in rats trained to self-administer sucrose. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 36 publications
3
38
1
Order By: Relevance
“…Together with positive effects on function, we also observed a recovery in brain connectivity with improved global network feature and increased DS density and PNNs. These changes at the cellular level after EE have also been shown in a rat model of neonatal hypoxia-ischemia with preserved DSs [53] and in an addiction-based model with increased PNN density [56]. The improvement at both behavioral and structural level is crucial to demonstrate the actual effect of EE therapy, identifying those functions and regions more sensitive to its effects, and to support its implementation in clinical conditions.…”
Section: Discussionmentioning
confidence: 70%
“…Together with positive effects on function, we also observed a recovery in brain connectivity with improved global network feature and increased DS density and PNNs. These changes at the cellular level after EE have also been shown in a rat model of neonatal hypoxia-ischemia with preserved DSs [53] and in an addiction-based model with increased PNN density [56]. The improvement at both behavioral and structural level is crucial to demonstrate the actual effect of EE therapy, identifying those functions and regions more sensitive to its effects, and to support its implementation in clinical conditions.…”
Section: Discussionmentioning
confidence: 70%
“…Nor were there sucrose craving incubation-related changes in neuroplasticityrelated brain derived neurotrophic factor protein levels (Grimm et al, 2003) in several brain regions examined. Finally, incubation of sucrose craving was not associated with changes in cortical (prelimbic, infralimbic, orbitofrontal) perineuronal net densities (Slaker, Barnes, Sorg, & Grimm, 2016). Serotonin 2C receptors have been associated with appetite (Halford & Harrold, 2012).…”
Section: Molecular Studiesmentioning
confidence: 84%
“…Serotonin 2C receptors have been associated with appetite (Halford & Harrold, 2012). Finally, incubation of sucrose craving was not associated with changes in cortical (prelimbic, infralimbic, orbitofrontal) perineuronal net densities (Slaker, Barnes, Sorg, & Grimm, 2016). These densities are hypothesized to be recruited to "stabilize" synapses and have been related to memory formation and retention (Slaker et al, 2018).…”
Section: Molecular Studiesmentioning
confidence: 99%
“…PNNs are modified by a variety of stimuli, including cocaine exposure [34,59], cocaine-CPP acquisition [21], alcohol [60,61], nicotine self-administration [62], heroin self-administration [63], sleep deprivation [40],environmental enrichment [64], and consumption of high fat diets [32]. A majority of PV FSIs within the PL PFC are surrounded by PNNs, and previous work by our group has shown that the amount of cocaine exposure differentially affected PNN and PV expression [34].…”
Section: Discussionmentioning
confidence: 99%